OPTN/SRTR 2012 Annual Data Report: Heart. Issue 1 (January 2014) - Colvin‐Adams, M.; Smithy, J. M.; Heubner, B. M.; Skeans, M. A.; Edwards, L. B.; Waller, C.; Schnitzler, M. A.; Snyder, J. J.; Israni, A. K.; Kasiske, B. L.
ABSTRACT The number of heart transplants performed annually continues to increase gradually, and the number of adult candidates on the waiting list increased by 25% from 2004 to 2012. The heart transplant rate among active adult candidates peaked at 149 per 100 wait‐list years in 2007 and has been declining since; in 2012, the rate was 93 heart transplants per 100 active wait‐list years. Increased waiting times do not appear to be correlated with an overall increase in wait‐list mortality. Since 2007, the proportion of patients on life support before transplant increased from 48.6% to 62.7% in 2012. Medical urgency categories have become less distinct, with most patients listed in higher urgency categories. Approximately 500 pediatric candidates are added to the waiting list each year; the number of transplants performed each year increased from 274 in 1998 to 372 in 2012. Graft survival in pediatric recipients continues to improve; 5‐year graft survival for transplants performed in 2007 was 78.5%. Medicare paid for some or all of the care for nearly 40% of heart transplant recipients in 2010. Heart transplant appears to be more expensive than ventricular assist devices for managing end‐stage heart failure, but is more effective and likely more cost‐effective.